The Effect of Rupiah Exchange Rate Fluctuations on the Financial Statements of Listed Companies on the IHSG in the Era of Digital Economy - Pranata, Natasha Anjanette; Widyasari, Della; Kustiwi, Irda Agustine (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study examines the impact of Rupiah exchange rate fluctuations on the financial statements of companies listed on the Indonesia Stock Exchange (IHSG) in the digital economy era. Using a descriptive quantitative approach, the research analyzes secondary data from 2019 to 2023, focusing on key financial indicators such as net income, Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER). The findings show that significant Rupiah depreciation, especially during the COVID-19 pandemic, negatively affected profitability and increased financial risk, particularly for companies dependent on imports or foreign currency debt. Conversely, export-oriented companies benefited from local currency gains. The study also highlights the importance of digital financial reporting systems and hedging strategies in enhancing corporate resilience. Recommendations include improving exchange rate risk management, diversifying revenue streams, and strengthening local supply chains. This research provides insights for corporate decision-makers and investors in navigating currency volatility in a digitized economic environment.